Legal Aspect of an Agreement Cancellation in the State of Majeure Force during the Pandemic Covid-19 - Mifta Hulzannah; Sriono Sriono; Elviana Sagala (Budapest International Research and Critics University, 2021)
Many parties can cancel an agreement or contract during the Covid-19 pandemic in Indonesia. WHO Director General, Tedros Adhanom Ghebreyesus determined the status of Corona Virus Disease 2019 (Covid-19) as a Pandemic This happened because the government issued Presidential Decree No. 12 of 2020 concerning the Determination of Disaster in the Spread of Corona Virus Disease 2019 (COVID-19) as a National Disaster. The covid-19 pandemic falls into the force majeure category or a state of force because it causes the economic sector to experience a decline. The community cannot do work as usual, all activities carried out are very limited. A contract is an agreement made by the parties in written form. An agreement is an act that binds one or more people to one or more people. This event resulted in a legal relationship between the parties, which included rights and obligations. Circumstances compel or force majeure may be earthquakes, fires, floods, landslides, wars, military coups, embargoes, epidemics, and so forth. In the time of the corona pandemic which is currently hitting all parts of the world, of course, it has an impact on the implementation of an agreement / contract. The purpose of this paper is to examine the force majeure in an agreement that occurs during the corona virus pandemic, which cannot automatically be used as a reason for cancellation of an agreement / contract, but can be used as a way to negotiate in canceling or changing the contents of the agreement / contract. The contract / agreement is canceled unilaterally without regard to the sense of justice, in accordance with Article 1338 paragraph (1) of the Civil Code, it is stated that the contract is a law for the parties. So the cancellation of the contract with due regard to aspects in the law and Article 1338 paragraph (1) of the Civil Code cannot be carried out in a covid-19 pandemic force majeure situation. The parties are required to carry out good faith in accordance with Article 1338 of the Civil Code by reviewing the agreement / contract or renegotiating by adding a contract clause to postpone carrying out obligations.